Leukocyte counts in three sympatric pack-ice seal species from the western Antarctic Peninsula - Leonardi, María Soledad (2019)
Global warming, and its consequences, constitute one of the main stressors for organisms worldwide, affecting different factors such as the geographic distribution and the abundance of parasites, which in turn can affect the immune system of their hosts, and vice versa. Therefore, it is important to have baseline information on immune parameters of organisms in order to make future comparisons within this changing ecological context. Here, we report on the leukocyte counts of the Antarctic pack ice seals, the crabeater (Lobodon carcinophaga), Weddell (Leptonychotes weddellii) and leopard (Hydrurga leptonyx) seals, sampled off the western Antarctic Peninsula. We captured and sampled seals in the pack ice off the Danco Coast, Antarctica in the austral summers, January to March, of 2015 and 2016. The leukocyte counts, along with the counts of each different leukocyte (e.g., basophil, neutrophil, eosinophil, lymphocyte and monocyte), were made from blood smears viewed under the light microscope. As a potential stress indicator, we examined whether seals with lice, so presumably under greater physiological stress, had changes in leukocyte counts, including higher ratios of neutrophil-to-lymphocytes (N/L ratio). Leukocyte counts were different among the seal species. While crabeater and Weddell seals had higher neutrophil counts, followed by lymphocyte counts, leopard seals had the reverse pattern. Basophil, eosinophil, and lymphocyte counts were higher in the leopard seal, while the N/L ratio, as well as the neutrophil counts, were higher for the crabeater seal. We show, for the Weddell seal, that the animals with lice were more likely to have higher N/L ratios. This suggests that future research into the potential of the N/L index as a stress indicator, that incorporates additional stress parameters including cortisol concentrations, oxidative damage, as well as other measures of immune function, is warranted for the pack ice seals. Our results are a first step towards establishing leukocyte count baselines for the Antarctic pack ice seals off the western Antarctic Peninsula.